Class of hemorrhagic shock is associated with progressive diastolic coronary flow reversal and diminished left ventricular function - Elansary, Noha N.; Stonko, David P.; Treffalls, Rebecca N.; Abdou, Hossam; Madurska, Marta J.; Morrison, Jonathan J. (Frontiers in Physiology, 2022)
Introduction: The relationship between coronary artery flow and left ventricular (LV) function during hemorrhagic shock remains unknown. The aim of this study was to quantify coronary artery flow directionality alongside LV function through the four classes of hemorrhage shock. Methods: Following baseline data collection, swine were exsanguinated into cardiac arrest via the femoral artery using a logarithmic bleed, taking each animal through the 4 classes of hemorrhagic shock based on percent bleed (class I: 15%; class II: 15-30%; class III: 30-40%; class IV: >40%). Telemetry data, LV pressure-volume loops, and left anterior descending artery flow tracings over numerous cardiac cycles were collected and analyzed for each animal throughout. Results: Five male swine (mean 72 ± 12 kg) were successfully exsanguinated into cardiac arrest. Mean LV end-diastolic volume, end-diastolic pressure, and stroke work decreased as the hemorrhagic shock class progressed (P<0.001). The proportion of diastole spent with retrograde coronary flow was also associated with class of hemorrhagic shock (mean 5.6% of diastole in baseline, to 63.9% of diastole in class IV; P<0.0001), worsening at each class from baseline through class IV. Systemic vascular resistance and preload recruitable stroke work (PRSW) decreased significantly in classes II through IV (P<0.001). Conclusion: LV function progressively decreased, and the coronary arteries spent a greater proportion of diastole in retrograde flow with the progression of hemorrhagic shock. PRSW, a load-independent measure of inotropy, also worsened in severe hemorrhagic shock, indicating the mechanism extends beyond the drop in preload and afterload alone. Left-sided resuscitation methods following exsanguination cardiac arrest may potentially counteract retrograde coronary flow and improve contractility by targeting the coronary arteries specifically.